2020
DOI: 10.1136/oemed-2020-106439
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to cholinesterase inhibiting insecticides and blood glucose level in a population of Ugandan smallholder farmers

Abstract: ObjectivesThe risk of diabetes mellitus may be elevated among persons exposed to some pesticides, including cholinesterase-inhibiting insecticides (organophosphates and carbamates). The objective of this study was to investigate how acetylcholinesterase activity was associated with mean blood glucose levels among smallholder farmers in Uganda.MethodsWe conducted a short-term follow-up study among 364 small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Hence, more than 1000 HbA 1c analyses were conducted during the study. Study findings have been reported elsewhere [5,6].…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Hence, more than 1000 HbA 1c analyses were conducted during the study. Study findings have been reported elsewhere [5,6].…”
Section: Methodssupporting
confidence: 62%
“…Point-of-care devices for the measurement of HbA 1c exist and have the potential to simplify data collection for studies of diabetes mellitus in such settings. Our partners and we recently carried out an epidemiological study on glycemic regulation in Uganda [5,6]. Our main outcome was HbA 1c , determined by the point-of-care device HemoCue HbA1c 501 (HemoCue AB, Ä ngelholm, Sweden, www.hemocue.com).…”
Section: Introductionmentioning
confidence: 99%
“…The PEXADU project population has a relatively high exposure to pesticides due to a lack of training on proper handling of pesticides and poor use of personal protective equipment. 14 Further studies are needed to investigate whether similar effects can be demonstrated in lower-exposed populations.…”
Section: Discussionmentioning
confidence: 98%
“…The study was conducted as part of the 'Pesticide Exposure, Asthma and Diabetes in Uganda' (PEXADU) project, 14 a shortterm cohort study among members of two organisations of smallholder farmers from the Wakiso District in central Uganda-one for conventional farmers, and one for farmers working towards organic certification. We recruited participants from these two organisations to minimise confounding from sociodemographic variables while maximising insecticide exposure contrast.…”
Section: Methodsmentioning
confidence: 99%
“…Data was collected as a part of the "Pesticide Exposure, Asthma and Diabetes in Uganda" (PEXADU) project, which was a study on the possible associations between pesticide exposure, pulmonary function and diabetes in a cohort of smallholder farmers in Uganda [5][6][7]. Details regarding participant recruitment and inclusion/exclusion have been presented elsewhere [5][6][7]. In brief, we recruited 364 farmers from the Wakiso District in central Uganda with the help of two local farmer's organizations.…”
Section: Study Populationmentioning
confidence: 99%